DNA variants in DHFR gene and response to treatment in children with childhood B ALL: revisited in AIEOP-BFM protocol. (January 2018) - Ceppi, Francesco; Gagné, Vincent; Douyon, Laurance; Quintin, Camille J; Colombini, Antonella; Parasole, Rosanna; Buldini, Barbara; Basso, Giuseppe; Conter, Valentino; Cazzaniga, Giovanni; Krajinovic, Maja
Aim: We have previously reported an association of dihydrofolate reductase promoter polymorphisms with reduced event-free survival in childhood acute lymphoblastic leukemia (ALL) patients treated with Dana Farber Cancer Institute protocol. Here, we assessed whether these associations are applicable to other protocol, based on different methotrexate doses.Methods: Genotypes for six tag polymorphisms and resulting haplotypes were analyzed for an association with ALL outcome.Results: The association was found with the polymorphisms A-680C, A-317G and C-35T in high-risk group patients. Carriers of haplotype *1 had a remarkably higher risk of events compared with noncarriers and a lower probability of event-free survival (21.4 vs 81.3%).Conclusion: The role of DHFR variants in predicting the outcome of childhood ALL extends beyond single-treatment protocol and can be useful biomarker in personalizing treatment.